The effect of body mass index on maternal and perinatal outcomes in COVID-19 infection during pregnancy and postpartum: Secondary analysis from the REBRACO cohort study - Sardinha, Thais G.; Lajos, Giuliane J.; Souza, Renato T.; Cecatti, Jose G.; Luz, Adriana G.; Oppermann, Maria Lúcia R.; Pacagnella, Rodolfo C.; Ribeiro-Do-Valle, Carolina C.; Nobrega, Guilherme M.; Griggio, Thayna B.; Charles, Charles M.; Silveira, Carla; et al. (Wiley, 2024)
Objectives: To compare maternal and perinatal outcomes among women with obesity, overweight, and normal body mass index, associated with COVID-19 infection during pregnancy and postpartum. Method: Prospective Cohort Study, within the REBRACO (Brazilian Network of COVID-19 in Pregnancy) multicenter initiative. Confirmed positive cases of SARS-CoV-2 were included, and women categorized into three groups according to their pre-pregnancy BMI: obesity (BMI ≥ 30), overweight (BMI <30 but >25), and normal BMI. Sociodemographic, clinical, and obstetric characteristics and different maternal and perinatal outcomes were compared, and a multiple regression analysis was performed to investigate factors independently associated with adverse maternal and perinatal outcomes. Results: Two hundred eighty-nine women positive for SARS-CoV-2 infection were considered, and 202 had available data on maternal BMI for the current analysis. Overall, 72 (35.6%)obese, 68 (33.6%) overweight, and 60 (29.7%) normal BMI. Obesity was associated with increased adverse clinical outcomes including sepsis (P = 0.02), acute respiratory distress syndrome (P = 0.002), and the need for mechanical ventilation (P = 0.044). Considering perinatal outcomes, a multiple regression model confirmed obesity as an independent factor associated with adverse results (adjusted odds ratio 3.73, 95% CI 1.54–9.08). Conclusion: Obesity and overweight were associated with worse clinical outcomes, severe/critical COVID-19, and adverse perinatal outcomes.
Keywords: COVID-19; obesity; overweight; postpartum; pregnancy